Tasten in het duister - Limpach, Rémy (Amsterdam University Press, 2023)
In the Indonesian war of independence, which had a strong guerrilla war character, intelligence was decisive for achieving military successes. No wonder that the Netherlands and the Republic of Indonesia waged a fierce intelligence battle between 1945 and 1949. Nevertheless, not much is known about the personnel, organization and working methods of the Dutch military intelligence services, which were to function as the eyes and ears of the army. This study examines this violent confrontation for intelligence in detail. To what extent have the Dutch services used torture and other forms of extreme violence? And why? How accurate was the intelligence they gathered about the Indonesian forces? What effects did their reports have on Dutch actions in the field – and on the decision-making of higher echelons? The tug-of-war over the crucial cooperation of the population and the extremely violent or otherwise violent actions of the Indonesian intelligence services are also discussed. The course of the espionage war is explained based on the interactions between the Dutch and Indonesian services, which continuously tried to outsmart each other. This book shows that this grim and complex struggle behind the scenes had a major – and so far underexposed – impact on the Dutch-Indonesian war.